In Vitro evaluation of cockle shell-based calcium carbonate aragonite polymorph nanoparticle with surface functionalization for drug delivery applications - Mohd Abd Ghafar, Syairah Liyana (2016)
Drug delivery is a current biomedical application employing nano-sized particles. In line with current global interest, employing nature-based materials to construct delivery carriers has been highly preferable due to their environmental friendly, availability, low cost, and good natural mineral purity. Cockle (Anadara granosa) shells was reported to contain comparable mineral compositions to vertebrates bone with high calcium carbon and no evident presence of heavy metal elements with good quality and pure calcium carbonate aragonite crystals. In order to meet stringent qualities of drug carrier for drug delivery applications, an improved synthesis method incorporated with surface functionalization was developed to produce nanoparticles with high homogeneity in size and shape. The study aimed at evaluating the physicochemical characteristics of surface functionalized cockle shell-based calcium carbonate aragonite nanoparticle and its potentials as delivery agent. Cockle shell micron-sized powder was converted into nano-sized particles through a mechanical stirring process in the presence of dodecyl dimethyl betaine (BS-12). The effect of BS- 12 surfactant on the surface property of cockle shell-based calcium carbonate aragonite nanoparticles was analyzed through pH evaluation, Fourier Transform Infrared (FTIR) and X-ray diffraction (XRD) analyzes. Transmission Electron Microscopy (TEM) and Field Emission Scanning Electron Microscopy (FESEM) demonstrated agglomeration of nanoparticles after the addition of surfactant. However, with calcium ion adsorption onto the surface of cockle shell-based calcium carbonate aragonite, the dispersion of the nanoparticles has improved as shown by the increase in zeta potential. Purification technique further enhanced the overall distribution of nanoparticles towards more refined size range of less than 100 nanometers, which is favorable for drug delivery applications. The purity of aragonite phase and chemical functionality were verified by FTIR and X-ray diffraction (XRD) analyzes. In vitro biological response on human fetal osteoblast (hFOB 1.19) cell line demonstrated that surface functionalization could decrease cytotoxicity. Surface functionalized cockle shell-based calcium carbonate aragonite nanocarrier showed better capacity to load drug molecules and was able to sustain incorporation of some drug molecules up to three days in vitro. Both the cockle shell-based nanocarrier samples were sensitive to pH changes as they released more drug compounds in the acidic environment of pH 6.4 than pH 7.4. This new delivery agent from cockle shells may provide an alternative source for calcium carbonate aragonite polymorph nanoparticles as an efficient drug carrier for therapeutic applications.